PENGARUH PROFITABILITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY (STUDI PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019) - Kriestince, Denada Sari Puspita; Hartono, Arif; Ulfa, Ika Farida (Jurnal Ekonomi Syariah Darussalam, 2022)
This study examines the effect of Profitability, Solvency, Firm Size on Audit Delay. The subjects of this study are automotive companies listed on the Indonesia Stock Exchange. This study tested from 2017 to 2019. The sample in this study consisted of 32 and obtained 12 companies that met the criteria. The sampling method in this study used the purposive sampling method. Regression analysis in this study using Multiple Linear Regression Analysis. Meanwhile, to test the hypothesis using t test and F test. The results of this study partially indicate that profitability has a positive effect on audit delay. This means that Ho1 is accepted, Ha1 is rejected. The results of the second hypothesis Solvency have a positive and significant effect on Audit Delay, it means that H02 is accepted and Ha2 is rejected. The results of the third hypothesis that Firm Size has a negative and significant effect on Audit Delay, it means that H03 is rejected and Ha3 is accepted. The results of the fourth hypothesis Profitability, solvency, and firm size have a significant effect on Audit Delay, it means that H04 is accepted and Ha4 is rejected.